Pengaruh Persepsi & Pengetahuan terhadap Penerapan Gaya Hidup Frugal Living pada Mahasiswa Universitas Diponegoro - Shafira, Orchita; Fadhlullah, Muhammad (Ikatan Sarjana Komunikasi Indonesia, 2025)
Every individual has inherent needs that must be fulfilled. These needs are influenced by an individual's lifestyle. One such lifestyle is frugal living, a lifestyle characterized by thriftiness and moderation. Frugal living does not equate to stinginess but rather involves avoiding excessive spending and consumption. This study aims to explain the influence of students' perceptions and knowledge of frugal living on their adoption of this lifestyle at Diponegoro University. Employing a quantitative explanatory research design, data was collected through a survey using questionnaires and analyzed using multiple linear regression. The findings reveal a significant influence of perceptions of frugal living on the adoption of this lifestyle among students (t: 5,387). However, there was no significant influence of knowledge of frugal living on the adoption of this lifestyle (t: 1,457). Nevertheless, combined, perceptions and knowledge of frugal living had a significant influence on the adoption of the frugal living lifestyle among students (f: 44,343), accounting for 44% of the variance. This is categorized as a moderate influence, suggesting a strong tendency towards influence.